Sharing the fruits of progress - Weng, Jeng-Yih; Chin, Roy (China : Kwang Hwa Mass Communications)
Focused on Taiwan's social economic, and political progress-and its desire to share the fruits of its progress-it deserves to become a more integral part of the world community.
Writer, Yakhoven Ku
Narrator: Earl Wevan
Keywords: Fruit -- Taiwan; Fruit -- China; Horticultural crops